Effect of Pinching on Growth, Flowering, and Yield of African Marigold (Tagetes erecta L.) cv. Calcutta Local - Sedhai, Ranjana; Katel, Shambhu; Adhikari, Anju (Fundamental and Applied Agriculture, 2024)
The single factor field experiment was laid out in a Randomized Complete Block Design (RCBD) with 5 treatments (T1-no pinching, T2-pinching at 10 DAT, T3-pinching at 20 DAT, T4-pinching at 30 DAT, and T5- pinching at 40 DAT) and four replications. Five plants were randomly selected from each treatment to record growth, flowering parameters, and yield of marigold. Among the treatments, T1 (no pinching) recorded the maximum plant height (89.05 cm), earliest bud initiation (29.75 days), the earliest appearance of the first flower (40.25 days), and minimum days to 50% flowering (50 days). Similarly, the maximum flower diameter (5.53 g), fresh weight (5.08 g), and dry weight of the flower (2.11 g) were also recorded with this treatment. Further, the highest number of primary branches per plant (19.25), secondary branches per plant (46.25), plant spread (59.20 cm), and the highest number of flowers (124.96), flower yield per plant (549.9 g), flower yield per plot (8.25 kg) and total flower yield (229.14 q/ha) were recorded at T5 (pinching at 40 DAT). Hence, it can be concluded that pinching at 40 DAT is the most effective practice for yield and number of flowers and no pinching can be recommended if early and large sized flowers are required.